Accelerographic Monitoring System of the Earthquake Engineering Laboratory - Moya Fernández, Aarón (2017)
The Earthquake Engineering Laboratory at the University of Costa Rica has been operating an automatic earthquake processing system that started in 2010. That system processes information gathered from over 120 digital triaxial accelerometers which are connected to the Internet. They are part of the laboratory’s strong motion network. When an earthquake occurs, the system calculates the location and magnitude of the event as well as the peak ground acceleration and velocity, and the response and design spectra for each of the stations that are online at the moment. The system is written in modular programming, and the full report that is generated takes about ten minutes. However, whenever a module finishes processing the data, the information is immediately uploaded to the website at www.lis.ucr.ac.cr.